Prevalence and distribution of dental anomalies of orthodontic patients among North Karnataka, India - Ramdurg, Praveenkumar; Mendegeri, Vijaylaxmi; K., Vanishree B.; Achanur, Mahantesh; Srinivas, Naveen (International Journal Of Community Medicine And Public Health, 2017)
Background: Dental anomalies are clinically evident abnormalities which can cause various dental problems, which may complicate orthodontic treatment planning. Clinical and radiological inspection play crucial role in identification of various anomalies. This study was carried over the period of 2.5 years to determine the prevalence and distribution of various morphological dental anomalies among orthodontic patients. Methods: Demographic details along with detailed medical, dental and family histories were obtained from every patient. In addition to the intraoral examination, dental panoramic radiograph were also evaluated for dental anomalies causing disturbance in number, size, form, and location of teeth. Patients with syndromes were not included in the study. Results: Out of 678 patients, dental anomalies were present in 161 (23.74%) patients. Hypodontia was the most prevalent dental anomaly occurring in 62 (9.1%). Microdontia was second most prevalent dental anomaly observed in 39 (5.7%). Other anomalies are hyperdontia, macrodontia, transposition, double teeth, taurodontism, Amelogenesis Imperfecta, Dentinogenesis Imperfecta and Dentine Displasia. Overall prevalence of dental anomalies is more common in males (26.45%). Class II malocclusion patients are having highest prevalence rate of dental anomalies followed by class I and class III Conclusion: Dental anomalies can lead to disturbance in occlusion. Orthodontists and oral radiologist have the responsibility to observe each patient carefully for various dental anomalies and have full knowledge of them as it can help them in planning treatment for these patients and executing them without any complications.